Tendoachilles reconstruction by a gastrosoleus turn-down flap: a case report - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath; Rajendran, Suresh (International Surgery Journal, 2021)
Acute and chronic rupture of the Achilles tendon (TA) is a common entity which requires surgery to either bridge the gap or to reinforce the strength of the repair or the tendon. This was done with a turn down flap of the gastrosoleus. Both the above conditions of acute and chronic rupture were usually misdiagnosed and mistreated. Hence, they presented to us late or with complications affecting the gait. Here, we presented a case of acute rupture of the TA presented late in a young female in which the defect was managed with a gastrosoleus aponeurosis turn down flap. Primary repair of acute TA rupture augmented with a gastrosoleus turn down flap provides a good outcome.